Prostaglandin Synthase 2/Cyclooxygenase 2 Gene Polymorphisms and Susceptibility to Urothelial Bladder Cancer in an Iranian Population - Kamyar Mansori; Mohammad Reza Nowroozi; Amirreza Farzin; Solmaz Ohadian Moghadam (Middle East journal of cancer, 2022)
Background: Prostaglandin-endoperoxide synthase 2, recognized as cyclooxygenase 2 (COX-2), is an important enzyme contributing to the generation of proinflammatory prostaglandins. It can play a role in increased tumor angiogenesis, apoptosis inhibition, metastasis, and invasion of tumors. Single nucleotide polymorphisms (SNPs) of the COX-2 promoter may associate with the cancer predisposition. In the present work, we aimed to explore whether SNPs of COX-2 gene affect both the risk of development and grade of bladder cancer.Method: This case-control study was performed and the genetic polymorphisms of six COX-2 SNPs including, intron 1 (rs2745557), intron 5 (rs16825748), intron 6 (rs2066826), T+8473C (rs5275), G-765 (rs20417), and A-1195G (rs68946) were genotyped in 80 healthy controls and 80 bladder cancer patients using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). To select independent prognostic factors, the univariate and multivariate analyses were implemented.Results: Univariate logistic regression model indicated a significant association between COX-2 765G>C heterozygous GC genotype and greater risk of bladder cancer (OR: 2.07; 95% CI: 1.03 - 4.15; P = 0.04). However, the multivariate logistic regression analysis showed no associations between COX-2 variants and bladder cancer development.Conclusion: We concluded that COX-2 polymorphisms do not contribute to the genetic susceptibility to urothelial bladder cancer in an Iranian population. However, the only genotype in which the frequency of alleles significantly differed between the two groups of high-grade tumors and low-grade tumors was COX-2 8473T> C (rs5275). Moreover, our findings showed that both smoking and family history of cancer play a role in susceptibility to bladder cancer.